Polyethylene-based composite non-woven fabric and preparation method thereof

By combining ultra-high molecular weight polyethylene fibers with modified epoxy resin and adding functional composite additives, a composite weft-free cloth with excellent impact resistance, heat resistance and flame retardant properties was prepared, which solved the problem of insufficient performance of the existing weft-free cloth.

CN119610816AActive Publication Date: 2025-03-14HEBEI ANTAI FUYUAN NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411816823.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The existing weft-free fabric has poor impact resistance, heat resistance and flame retardant properties, which limits its application range.

Method used

Ultra-high molecular weight polyethylene fiber is used to combine with modified epoxy resin, and by adding functional composite additives, including modified vermiculite and modified rubber, an adhesive with excellent bonding and flame retardant properties is formed, and a composite weft-free cloth is made by hot pressing.

Benefits of technology

It significantly improves the impact resistance, heat resistance and flame retardancy of composite weft-free fabrics, and enhances its application reliability in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119610816A_ABST
    Figure CN119610816A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and discloses composite non-woven cloth based on polyethylene and a preparation method thereof.The composite non-woven cloth is prepared from ultra-high molecular weight polyethylene fibers as a base material through hot pressing with an adhesive, and the adhesive is prepared from epoxy resin, a functional composite additive, a defoaming agent and a curing agent; the functional composite additive is added into the adhesive, so that the density and cohesion of the adhesive can be effectively enhanced, the binding force of the adhesive and ultra-high molecular weight polyethylene fibers is improved, the impact resistance of the composite non-woven fabric is further improved, and the situation that the service life of the non-woven fabric is shortened due to tearing caused by debonding and slippage of the fibers when the composite non-woven fabric is impacted is avoided; meanwhile, the heat resistance and the flame retardance of the adhesive can be improved, so that the safety and the reliability of the composite non-woven cloth are improved, the application range of the composite non-woven cloth is widened, and the application prospect is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a polyethylene-based composite non-woven fabric and a preparation method thereof. Background Art

[0002] Non-woven fabric, also known as unidirectional fabric, is lightweight, high-strength and has excellent protective properties. It is composed of two parts, one is a matrix composed of adhesive, and the other is high-performance fiber. Non-woven fabric is usually made by arranging fibers in parallel in one direction and bonding them with thermoplastic resin. The layers are crossed and pressed with thermoplastic resin. It is widely used in many fields, such as bulletproof materials, puncture-proof and cut-proof products, aerospace, sporting goods, filter materials, thermal insulation materials, electromagnetic shielding materials, etc. Therefore, the research and modification of non-woven fabric has important practical significance.

[0003] The high-performance fibers of non-woven fabrics generally include ultra-high molecular weight polyethylene fibers, aramid fibers, carbon fibers, etc. Among them, ultra-high molecular weight polyethylene fibers have excellent chemical resistance and can maintain stable performance in harsh chemical environments. They have low density, meet lightweight requirements, have good wear resistance, are not easy to break, have a regular structure, are easy to crystallize, and are easy to process. Therefore, they can be used as the preparation material of non-woven fabrics. Common adhesive matrices for non-woven fabrics generally include polyurethane, polyethylene, polypropylene, ethylene-propylene copolymer, polybutadiene, natural rubber, epoxy resin, styrene-butadiene adhesive, etc. Epoxy resin has good bonding properties with ultra-high molecular weight polyethylene fibers, which can make the fiber and adhesive have a tight structure, and can withstand greater loads after curing. The curing shrinkage is small, which can effectively reduce the dimensional change of the non-woven fabric and maintain stability. At the same time, epoxy resin has good processability, but There are still some shortcomings in using epoxy resin as the adhesive matrix of non-woven fabric. The impact resistance of epoxy resin is poor. When it is impacted by external force, the non-woven fabric may be damaged. At the same time, the heat resistance and flame retardancy of epoxy resin are poor, which limits the application of non-woven fabric. Patent No. CN103015041B discloses a preparation method of white carbon black reinforced ultra-high molecular weight polyethylene fiber composite non-woven fabric. By adding gas phase white carbon black, more energy generated when the bullet impacts the fiber can be absorbed, so that the bulletproof performance can be improved, and the overall heat resistance can be improved. However, the patent does not take into account the poor flame retardancy of ultra-high molecular weight polyethylene fiber composite non-woven fabric, which will limit the application of the composite non-woven fabric. Therefore, the present invention provides a polyethylene-based composite non-woven fabric with excellent impact resistance, heat resistance and flame retardancy, and has broad application prospects. Summary of the invention

[0004] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a polyethylene-based composite non-woven fabric and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A polyethylene-based composite non-woven fabric is made by hot pressing ultra-high molecular weight polyethylene fibers and an adhesive; the adhesive comprises the following raw materials in parts by weight: 30-45 parts of epoxy resin, 3-6 parts of functional composite additives, 1-4 parts of defoaming agents, and 9-12 parts of curing agents.

[0007] Furthermore, the preparation method of the functional composite additive is as follows:

[0008] Step 1: Preparation of modified vermiculite

[0009] Disperse vermiculite in dimethyl sulfoxide to form a uniform suspension, add a halogenated epoxy modifier and a catalyst, raise the temperature to 70-78°C, stir and react for 3-5 hours, cool to room temperature, filter, wash and dry to obtain modified vermiculite;

[0010] By adopting the above technical scheme, the hydroxyl groups on the surface of the vermiculite can react with the epoxy groups in the structure of the halogenated epoxy modifier under the action of a catalyst to obtain modified vermiculite with halogen substituents and hydroxyl groups generated by ring opening.

[0011] Step 2: Preparation of modified rubber

[0012] Add polysulfide rubber to tetrahydrofuran, stir evenly, add diethyl allyl phosphate and a photoinitiator, place the system under ultraviolet light for 1-2 hours, evaporate and remove the solvent, discharge the material, and obtain a modified rubber;

[0013] By adopting the above technical scheme, the polysulfide rubber structure contains active mercapto groups, which can undergo mercapto-ene click reaction with the alkenyl groups in the allyl diethyl phosphate structure under the irradiation of photoinitiators and ultraviolet lamps to obtain modified rubber.

[0014] Step 3: Preparation of functional composite additives

[0015] Add modified vermiculite to N,N-dimethylformamide, disperse evenly, introduce nitrogen protection, add modified rubber, raise the temperature to 65-70°C, stir evenly, add alkaline catalyst, raise the temperature to 70-80°C, keep the temperature under stirring for 4-6 hours, cool to room temperature, collect the product, wash and dry it to obtain the functional composite additive.

[0016] By adopting the above technical solution, the halogen substituents on the surface of the modified vermiculite can react with the mercapto groups in the modified rubber structure under the action of an alkaline catalyst to obtain a functional composite additive.

[0017] Furthermore, in step 1, the halogenated epoxy modifier is epichlorohydrin or epibromohydrin.

[0018] Furthermore, in step 1, the catalyst is boron trifluoride etherate.

[0019] Furthermore, in step 2, the photoinitiator is benzoin dimethyl ether or benzoin ethyl ether.

[0020] Furthermore, in step three, the alkaline catalyst is any one of potassium carbonate, sodium carbonate or potassium hydroxide.

[0021] Furthermore, the curing agent is diaminodiphenylmethane or diethylenetriamine; and the defoaming agent is polysiloxane.

[0022] A method for preparing a composite non-woven fabric based on polyethylene comprises the following steps:

[0023] Step 1: Add epoxy resin, functional composite additives, defoamer and curing agent into a high-speed mixer according to weight, stir and mix evenly for 30-60 minutes at a stirring rate of 200-500r / min to obtain an adhesive, and add the adhesive into the adhesive tank;

[0024] Step 2: The ultra-high molecular weight polyethylene fiber is immersed in a 30-35% ethanol solution for cleaning, after removing impurities, dried, evenly laid, transported to the glue tank by a traction machine, roller coated with adhesive, dried by a dryer, and then wound up by a winder to obtain an ultra-high molecular weight polyethylene fiber sheet;

[0025] Step 3: Cut the ultra-high molecular weight polyethylene fiber sheets, lay them orthogonally, and make a composite non-woven fabric by heating and pressurizing.

[0026] Furthermore, in the second step, the roller coating amount of the adhesive is 1-1.5 g / cm 2 .

[0027] Furthermore, in the third step, during the heating and pressurizing, the temperature is set to 90-110° C., the pressure is set to 10-15 MPa, and the hot pressing time is 15-30 min.

[0028] Beneficial effects of the present invention:

[0029] (1) The functional composite additive prepared by the present invention improves the compatibility problem between vermiculite and epoxy resin by organically modifying vermiculite, promotes the uniform dispersion of vermiculite in epoxy resin, reduces the probability of vermiculite agglomeration, and the good dispersion of vermiculite in epoxy resin enhances the bonding between vermiculite and epoxy resin. When subjected to external impact, stress transfer points are formed to effectively transfer stress and bear load. Vermiculite has a layered structure. When the interlayer structure is destroyed when subjected to impact, it will absorb a large amount of impact energy, which can improve the impact resistance. After being grafted with modified rubber, the functional composite additive can be used as a composite material. The polysulfide rubber in the functional composite additives can absorb and disperse external impact force and stress, prevent crack propagation, and play a role in toughening and improving impact resistance. At the same time, the hydroxyl groups in the functional composite additives can participate in the curing of the epoxy resin, cross-link with the epoxy resin molecular chains, form a polymer network structure, enhance the density of the structure, enhance the cohesion of the adhesive, and improve the bonding force between the adhesive and the ultra-high molecular weight polyethylene fiber, thereby greatly improving the impact resistance of the non-woven fabric, avoiding fiber debonding and slipping when impacted, causing tearing, and shortening the service life of the non-woven fabric.

[0030] (2) The layered structure of vermiculite in the functional composite additive can form a physical barrier layer, effectively slowing down heat transfer and having a heat-insulating effect. After the functional composite additive is cross-linked with the epoxy resin molecular chain, the heat resistance of the epoxy resin is improved, avoiding the decrease in the adhesion of the adhesive in a high-temperature environment, which leads to a decrease in the performance of the non-woven fabric. In addition, the flame-retardant sulfur element in the functional composite additive also introduces flame-retardant diethyl phosphate, which avoids the migration of small molecular flame retardants. During the combustion process, it can quickly form a dense carbon layer that is oxygen-insulated and heat-insulated to prevent the spread of fire. The layered structure of vermiculite can synergistically insulate, oxygen-insulate and flame-retardant, protect life and property safety, and improve the safety and reliability of the non-woven fabric.

[0031] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0033] Figure 1 is the infrared spectrum of the modified rubber in the present invention;

[0034] Figure 2 The scanning electron microscope images of the vermiculite and the functional composite additive in the present invention are shown in FIG. 1 , wherein (A) is vermiculite and (B) is the functional composite additive. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] The preparation methods of the functional composite additives in the following examples and comparative examples are as follows:

[0037] Step 1: Preparation of modified vermiculite

[0038] 4 g of vermiculite was dispersed in dimethyl sulfoxide to form a uniform suspension, 2.6 g of epichlorohydrin and 0.1 g of boron trifluoride ether were added, the temperature was raised to 75°C, and the reaction was stirred for 4 h. After cooling to room temperature, the mixture was filtered, washed, and dried to obtain modified vermiculite.

[0039] Step 2: Preparation of modified rubber

[0040] 6 g of polysulfide rubber was added to tetrahydrofuran, and after being stirred evenly, 2.3 g of diethyl allyl phosphate and 0.3 g of dimethyl benzoate were added, and the system was placed under ultraviolet light for 1 hour, and the solvent was evaporated to remove the material, and the modified rubber was obtained;

[0041] The samples were prepared by potassium bromide tableting method, and the modified rubber was tested by infrared spectrometer using Fourier transform infrared spectrometer. Figure 1 As shown in the figure, analysis shows that in the infrared spectrum of the modified rubber, 2560cm -1 The absorption peak of SH appeared at 1235 cm -1 The absorption peak of P=O appeared at 1186cm -1 The absorption peak of CSC appeared at 1088cm -1 The absorption peak of COC appeared at 1025cm -1 The absorption peak of PO appeared at .

[0042] Step 3: Preparation of functional composite additives

[0043] Add 3.2g of modified vermiculite to N,N-dimethylformamide, disperse evenly, introduce nitrogen protection, add 5.8g of modified rubber, raise the temperature to 70°C, stir evenly, add 0.8g of potassium carbonate, raise the temperature to 76°C, keep the reaction under stirring for 5h, cool to room temperature, collect the product, wash and dry to obtain the functional composite additive.

[0044] The morphology of vermiculite and functional composite additives was analyzed using a Hitach i S-4700 scanning electron microscope. Figure 2 It can be seen that (A) is vermiculite and (B) is a functional composite additive. Vermiculite is a layered structure with a relatively smooth surface, while the surface of the functional composite additive is uneven and has a partially coated structure, which is relatively rough. This is because the modified rubber reacts successfully with vermiculite and is coated on the surface of the vermiculite.

[0045] Example 1

[0046] Preparation of composite non-woven fabric

[0047] Step 1: Add 30g epoxy resin, 3g functional composite additive, 1g polysiloxane defoamer and 9g diaminodiphenylmethane into a high-speed mixer, stir and mix them evenly for 30min at a stirring rate of 200r / min to obtain an adhesive, and add the adhesive into the adhesive tank;

[0048] Step 2: Immerse the ultra-high molecular weight polyethylene fiber in a 30% ethanol solution for cleaning, remove impurities, dry it, lay it evenly, transfer it to the glue tank with a traction machine, and roll the adhesive. The amount of adhesive rolled is 1g / cm 2 After being dried in a dryer, the fiber is rolled up by a winder to obtain an ultra-high molecular weight polyethylene fiber sheet;

[0049] Step 3: After cutting the ultra-high molecular weight polyethylene fiber sheets, they are stacked orthogonally, and heated and pressed with the temperature set to 90°C, the pressure set to 10MPa, and the hot pressing time set to 15 minutes to make a composite non-woven fabric.

[0050] Example 2

[0051] Step 1: Add 35g of epoxy resin, 4g of functional composite additives, 2g of polysiloxane defoamer and 10g of diaminodiphenylmethane into a high-speed mixer, stir and mix them evenly for 40min at a stirring rate of 300r / min to obtain an adhesive, and add the adhesive into the adhesive tank;

[0052] Step 2: Immerse the ultra-high molecular weight polyethylene fiber in a 32% ethanol solution for cleaning, remove impurities, dry it, lay it evenly, transfer it to the glue tank with a traction machine, and roll the adhesive. The amount of adhesive rolled is 1.2g / cm 2 After being dried in a dryer, the fiber is rolled up by a winder to obtain an ultra-high molecular weight polyethylene fiber sheet;

[0053] Step 3: After cutting the ultra-high molecular weight polyethylene fiber sheets, they are stacked orthogonally, and heated and pressed with the temperature set to 95°C, the pressure set to 12MPa, and the hot pressing time set to 20min to make a composite non-woven fabric.

[0054] Example 3

[0055] Step 1: Add 38g of epoxy resin, 5g of functional composite additive, 2g of polysiloxane defoamer and 10g of diaminodiphenylmethane into a high-speed mixer, stir and mix them evenly for 50min at a stirring rate of 400r / min to obtain an adhesive, and add the adhesive into the adhesive tank;

[0056] Step 2: Immerse the ultra-high molecular weight polyethylene fiber in a 34% ethanol solution for cleaning, remove impurities, dry it, lay it evenly, transfer it to the glue tank with a traction machine, and roll the adhesive. The amount of adhesive rolled is 1.4g / cm 2 After being dried in a dryer, the fiber is rolled up by a winder to obtain an ultra-high molecular weight polyethylene fiber sheet;

[0057] Step 3: After cutting the ultra-high molecular weight polyethylene fiber sheets, they are stacked orthogonally, and heated and pressed with the temperature set to 100°C, the pressure set to 14MPa, and the hot pressing time set to 25min to make a composite non-woven fabric.

[0058] Example 4

[0059] Step 1: Add 45g of epoxy resin, 6g of functional composite additives, 4g of polysiloxane defoamer and 12g of diaminodiphenylmethane into a high-speed mixer, stir and mix them evenly for 60 minutes at a stirring rate of 500r / min to obtain an adhesive, and add the adhesive into the adhesive tank;

[0060] Step 2: Immerse the ultra-high molecular weight polyethylene fiber in a 35% ethanol solution for cleaning, remove impurities, dry it, lay it evenly, transfer it to the glue tank with a traction machine, and roll the adhesive. The amount of adhesive rolled is 1.5g / cm 2 After being dried in a dryer, the fiber is rolled up by a winder to obtain an ultra-high molecular weight polyethylene fiber sheet;

[0061] Step 3: After cutting the ultra-high molecular weight polyethylene fiber sheets, they are stacked orthogonally, and heated and pressed with the temperature set to 110°C, the pressure set to 15MPa, and the hot pressing time set to 30min to make a composite non-woven fabric.

[0062] Comparative Example 1

[0063] Step 1: Add 38g of epoxy resin, 5g of vermiculite, 2g of polysiloxane defoamer and 10g of diaminodiphenylmethane into a high-speed mixer, stir and mix evenly for 50min at a stirring rate of 400r / min to obtain an adhesive, and add the adhesive into the adhesive tank;

[0064] Step 2: Immerse the ultra-high molecular weight polyethylene fiber in a 34% ethanol solution for cleaning, remove impurities, dry it, lay it evenly, transfer it to the glue tank with a traction machine, and roll the adhesive. The amount of adhesive rolled is 1.4g / cm 2 After being dried in a dryer, the fiber is rolled up by a winder to obtain an ultra-high molecular weight polyethylene fiber sheet;

[0065] Step 3: After cutting the ultra-high molecular weight polyethylene fiber sheets, they are stacked orthogonally, and heated and pressed with the temperature set to 100°C, the pressure set to 14MPa, and the hot pressing time set to 25min to make a composite non-woven fabric.

[0066] Comparative Example 2

[0067] Step 1: Add 38g of epoxy resin, 5g of polysulfide rubber, 2g of polysiloxane defoamer and 10g of diaminodiphenylmethane into a high-speed mixer, stir and mix evenly for 50min at a stirring rate of 400r / min to obtain an adhesive, and add the adhesive into the adhesive tank;

[0068] Step 2: Immerse the ultra-high molecular weight polyethylene fiber in a 34% ethanol solution for cleaning, remove impurities, dry it, lay it evenly, transfer it to the glue tank with a traction machine, and roll the adhesive. The amount of adhesive rolled is 1.4g / cm 2 After being dried in a dryer, the fiber is rolled up by a winder to obtain an ultra-high molecular weight polyethylene fiber sheet;

[0069] Step 3: After cutting the ultra-high molecular weight polyethylene fiber sheets, they are stacked orthogonally, and heated and pressed with the temperature set to 100°C, the pressure set to 14MPa, and the hot pressing time set to 25min to make a composite non-woven fabric.

[0070] Comparative Example 3

[0071] Step 1: Add 38g of epoxy resin, 5g of diethyl allyl phosphate, 2g of polysiloxane defoamer and 10g of diaminodiphenylmethane into a high-speed mixer, stir and mix evenly for 50min at a stirring rate of 400r / min to obtain an adhesive, and add the adhesive into the adhesive tank;

[0072] Step 2: Immerse the ultra-high molecular weight polyethylene fiber in a 34% ethanol solution for cleaning, remove impurities, dry it, lay it evenly, transfer it to the glue tank with a traction machine, and roll the adhesive. The amount of adhesive rolled is 1.4g / cm 2 After being dried in a dryer, the fiber is rolled up by a winder to obtain an ultra-high molecular weight polyethylene fiber sheet;

[0073] Step 3: After cutting the ultra-high molecular weight polyethylene fiber sheets, they are stacked orthogonally, and heated and pressed with the temperature set to 100°C, the pressure set to 14MPa, and the hot pressing time set to 25min to make a composite non-woven fabric.

[0074] Comparative Example 4

[0075] Step 1: Add 38g of epoxy resin, 2g of polysiloxane defoamer and 10g of diaminodiphenylmethane into a high-speed mixer, stir and mix evenly for 50min at a stirring rate of 400r / min to obtain an adhesive, and add the adhesive into the adhesive tank;

[0076] Step 2: Immerse the ultra-high molecular weight polyethylene fiber in a 34% ethanol solution for cleaning, remove impurities, dry it, lay it evenly, transfer it to the glue tank with a traction machine, and roll the adhesive. The amount of adhesive rolled is 1.4g / cm 2 After being dried in a dryer, the fiber is rolled up by a winder to obtain an ultra-high molecular weight polyethylene fiber sheet;

[0077] Step 3: After cutting the ultra-high molecular weight polyethylene fiber sheets, they are stacked orthogonally, and heated and pressed with the temperature set to 100°C, the pressure set to 14MPa, and the hot pressing time set to 25min to make a composite non-woven fabric.

[0078] Performance Testing

[0079] The composite non-woven fabrics prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were prepared into samples that met the test requirements. According to GB / T 32497-2016, the V50 values ​​of the samples were tested. The samples were placed under natural conditions for 6 months. According to GB / T 5454-1997, the limiting oxygen index of the samples was tested. The samples were placed in an environment of 115° C. for 800 hours, and the changes in the appearance of the samples were observed. The test results are shown in the following table:

[0080] V50 value (m / s) Limiting oxygen index (%) High temperature treatment changes Example 1 590 28.3 No change Example 2 593 28.5 No change Example 3 598 29.2 No change Example 4 595 28.8 No change Comparative Example 1 570 18.4 Slight yellowing Comparative Example 2 566 19.6 Severe yellowing Comparative Example 3 503 20.1 Severe yellowing and wrinkling Comparative Example 4 492 16.3 Severe yellowing and wrinkling

[0081] It can be seen from the above table that the composite non-woven fabrics prepared in Examples 1 to 4 of the present invention have excellent impact resistance, flame retardant properties and heat resistance. In Comparative Example 1, vermiculite is added to the preparation of the adhesive, and it is directly added without modification, resulting in agglomeration, which has limited improvement in impact resistance and heat resistance, and poor flame retardant effect; in Comparative Example 2, polysulfide rubber is added to the preparation of the adhesive, and the impact resistance, heat resistance and flame retardant properties are poor; in Comparative Example 3, allyl diethyl phosphate is added to the preparation of the adhesive, and small molecule flame retardants are easy to migrate, resulting in decreased flame retardant properties, poor impact resistance and heat resistance; In Comparative Example 4, no functional composite additives are added during the preparation of the adhesive, and the test results are poor.

[0082] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A composite non-woven fabric based on polyethylene, characterized in that: It is made by hot pressing ultra-high molecular weight polyethylene fiber and adhesive; the adhesive comprises the following raw materials in parts by weight: 30-45 parts of epoxy resin, 3-6 parts of functional composite additives, 1-4 parts of defoaming agent, and 9-12 parts of curing agent.

2. The polyethylene-based composite non-woven fabric according to claim 1, characterized in that: The preparation method of the functional composite additive is as follows: Step 1: Preparation of modified vermiculite Disperse vermiculite in dimethyl sulfoxide to form a uniform suspension, add a halogenated epoxy modifier and a catalyst, raise the temperature to 70-78°C, stir and react for 3-5 hours, cool to room temperature, filter, wash and dry to obtain modified vermiculite; Step 2: Preparation of modified rubber Add polysulfide rubber to tetrahydrofuran, stir evenly, add diethyl allyl phosphate and a photoinitiator, place the system under ultraviolet light for 1-2 hours, evaporate and remove the solvent, discharge the material, and obtain a modified rubber; Step 3: Preparation of functional composite additives Add modified vermiculite to N,N-dimethylformamide, disperse evenly, introduce nitrogen protection, add modified rubber, raise the temperature to 65-70°C, stir evenly, add alkaline catalyst, raise the temperature to 70-80°C, keep the temperature under stirring for 4-6 hours, cool to room temperature, collect the product, wash and dry it to obtain the functional composite additive.

3. The polyethylene-based composite non-woven fabric according to claim 2, characterized in that: In step 1, the halogenated epoxy modifier is epichlorohydrin or epibromohydrin.

4. The polyethylene-based composite non-woven fabric according to claim 2, characterized in that: In step 1, the catalyst is boron trifluoride etherate.

5. The polyethylene-based composite non-woven fabric according to claim 2, characterized in that: In step 2, the photoinitiator is benzoin dimethyl ether or benzoin ethyl ether.

6. The polyethylene-based composite non-woven fabric according to claim 2, characterized in that: In step 3, the alkaline catalyst is any one of potassium carbonate, sodium carbonate or potassium hydroxide.

7. The polyethylene-based composite non-woven fabric according to claim 1, characterized in that: The curing agent is diaminodiphenylmethane or diethylenetriamine; and the defoaming agent is polysiloxane.

8. A method for preparing a polyethylene-based composite non-woven fabric as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Add epoxy resin, functional composite additives, defoamer and curing agent into a high-speed mixer according to weight, stir and mix evenly for 30-60 minutes at a stirring rate of 200-500r / min to obtain an adhesive, and add the adhesive into the adhesive tank; Step 2: The ultra-high molecular weight polyethylene fiber is immersed in a 30-35% ethanol solution for cleaning, after removing impurities, dried, evenly laid, transported to the glue tank by a traction machine, roller coated with adhesive, dried by a dryer, and then wound up by a winder to obtain an ultra-high molecular weight polyethylene fiber sheet; Step 3: Cut the ultra-high molecular weight polyethylene fiber sheets, lay them orthogonally, and make a composite non-woven fabric by heating and pressurizing.

9. The method for preparing a composite non-woven fabric based on polyethylene according to claim 8, characterized in that: In the second step, the roller coating amount of the adhesive is 1-1.5 g / cm 2 .

10. The method for preparing a composite non-woven fabric based on polyethylene according to claim 8, characterized in that: In the third step, during the heating and pressurizing, the temperature is set to 90-110° C., the pressure is set to 10-15 MPa, and the hot pressing time is 15-30 min.

Citation Information

Patent Citations

  • Preparation method of white carbon black enhanced UHMWPE (ultrahigh molecular weight polyethylene) fiber composite non-weft fabric

    CN103015041B

  • Process for preparing ultra-strong polythene weft-less cloth with high-performance inorganic nanometer materials

    CN101722698A

  • Impact-resistant non-woven cloth compound material and preparation method thereof

    CN106427178A

  • High-performance PE fiber composite non-woven cloth and production process thereof

    CN115559061A

  • Epoxy resin composition

    JP2014101397A

Cited By

  • Deep coal bed gas well cementation cement paste and preparation method thereof

    CN120757336A